Power in Foucault: analytical bases for the study of organizations - Yela Gómez, Jeysson; Hidalgo Romero, Clara (Cuadernos de Administración, 2010)
This article is the result of an initial concern about the existing concept of power in organizational studies as a tool for understanding the dynamics of today’s business organizations. Approaches to the power in such organizations suggest its appropriation from an instrumental and pragmatic perspective, since attention has focused on issues related to how to gain power and its use efficiently and strategically from the directors and management. With this background, the  research intends to show a theoretical analysis of the notion of power in Michel Foucault as a reference to overcome the traditional boundaries of organizational thinking. For this purpose, we performed an analysis and synthesis of the approaches of Foucault about power, particularly in the works Governmentality, The Subject and Power, Microphysics of Power, Discipline and Punish and The Will to Knowledge, through literature review and systematization of the development of prominent writers who have concerned about the concept of power in the organizational context. The last part of the text is devoted to reflection and problematization of power in business organization, of its efforts to establish a control and a discipline to organize and regulate workers, and so get them its maximum contribution to achieving organizational objectives. Finally, Foucault allows understanding how disciplinary power is integrated into the daily life of the organization, its processes and social relations between its members, thus shaping a possible alternative study of organizations, of how subjectivity breaks -and suffers the pounding of- the power relations creating individuals that reproduce the conditions of which they are subjected.